Social capital and organisational competitiveness in the Information and Communications Technology sector : a validation of the "Opportunity-Motivation-Ability" model - Wilson-Prangley, Anthony (University of Pretoria, 2016)
Mini Dissertation (MBA)--University of Pretoria, 2015.